(untitled) (The Pakistan Development Review, 1994)
The process of urbanisation is fed by the migration of people from the rural to the urban areas. Among the several reasons why people move to cities, the following are considered to be the most important: modernisation in agriculture and the resultant labour displacement, rapid industrial development, and concentration of land in a few hands; also the lack of non-agricultural jobs in the rural areas and the increase in population. The immigrants face a different environment in the cities and generally find it difficult to adjust to the setting with a new set of social relations. The poor unskilled labour coming from the rural areas to settle in the cities at any cost finds its way to the squalor of the slum areas. The resultant population pressure forces the people of these areas to face severe problems not only in terms of inadequate wages and incomes but also in terms of their relations with their spouses, children, friends, relatives, and neighbours. In the slum areas thus growing, it is not possible for the planning and development authorities, despite their extensive efforts, to provide to all the inhabitants such social services and amenities as education and health facilities, parks, playgrounds, and safe drinkingwater. Left without the amenities of developed urban areas, these inhabitants struggle for survival.